Pastplay Teaching and Learning History with Technology - Kee, Kevin B. (Kevin Bradley), 1969-; Project Muse; Project Muse. (Project Muse, 2014)
In the field of history, the Web and other technologies have become important tools in research and teaching of the past. Yet the use of these tools is limited--many historians and history educators have resisted adopting them because they fail to see how digital tools supplement and even improve upon conventional tools (such as books). In Pastplay, a collection of essays by leading history and humanities researchers and teachers, editor Kevin Kee works to address these concerns head-on. How should we use technology? Playfully, Kee contends. Why? Because doing so helps us think about the past in new ways; through the act of creating technologies, our understanding of the past is re-imagined and developed. From the insights of numerous scholars and teachers, Pastplay argues that we should play with technology in history because doing so enables us to see the past in new ways by helping us understand how history is created; honoring the roots of research, teaching, and technology development; requiring us to model our thoughts; and then allowing us to build our own understanding.
What has mystery got to do with it? / Ruth Sandwell and John Sutton Lutz -- "Why can't you just tell us?" : learning Canadian history with the Virtual Historian / Stephane Levesque -- Interactive worlds as educational tools for understanding Arctic life / Richard Levy and Peter Dawson -- Tecumseh lies here : goals and challenges for a pervasive history game in progress / Timothy Compeau and Robert MacDougall -- The hermeneutics of screwing around; or what you do with a million books / Stephen Ramsay -- Abort, retry, pass, fail : games as teaching tools / Sean Gouglas, Mihaela Ilovan, Shannon Lucky, and Silvia Russell -- Ludic algorithms / Bethany Nowviskie -- Making and playing with models : using rapid prototyping to explore the history and technology of stage magic / William J. Turkel and Devon Elliott -- Contests for meaning : playing King Philip's War in the twenty-first century / Matthew Kirscenbaum -- Rolling your own : on modding commercial games for educational goals / Shawn Graham -- Simulation games and the study of the past : classroom guidelines / Jeremiah McCall -- Playing into the past : reconsidering the educational promise of public history exhibits / Brenda Trofanenko -- Teaching history in an age of pervasive computing : the case for games in the high school and undergraduate classroom / Kevin Kee and Shawn Graham -- Victorian SimCities : playful technology on Google Earth / Patrick Dunae and John Sutton Lutz -- True facts or false facts--which are more authentic / T. Mills Kelly.
"Digital culture books"--Series title page.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: History -- Computer-assisted instruction; History -- Study and teaching (Higher) -- Technological innovations; History -- Study and teaching -- Technological innovations; Electronic books; Electronic books